SISTEM PENDUKUNG KEPUTUSAN MENGGUNAKAN METODE PROMETHEE (STUDI KASUS : STASIUN PENGISIAN BAHAN BAKAR UMUM) - Hendy Ayusta Yudha; Bambang Yuwono; Frans Richard Kodong (Telematika, 2011)
The research was conducted based on the need for assistive devices for people to determine the location of the establishment of public refueling stations. Aids in the form of decision support systems. There are six criteria for determining the location of the establishment of broad land, land prices, traffic density, many transportation routes, distance to other retail outlets and administration. While the location is also six. In this study has successfully built a decision support system to determine the location of the establishment of public refueling stations using the method promethee. Hasi of this system of ranking based on the size of the leaving flow, entering flow, and net flow.